Number of women on boards of PLCs, GLCs discouraging - New Sarawak, Tribune (New Sarawak Tribune, 2011)
SINTOK: The percentage of women appointed to high positions in the corporate and public sectors is discouraging according to the NAM Institute for the Empowerment of Women (NIEW).